1998
DOI: 10.1176/ajp.155.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Carbamazepine for Agitation and Aggression in Dementia

Abstract: This controlled study showed significant short-term efficacy of carbamazepine for agitation with generally good safety and tolerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
159
0
12

Year Published

1999
1999
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 370 publications
(173 citation statements)
references
References 22 publications
2
159
0
12
Order By: Relevance
“…They often do not present as discrete psychiatric diagnoses but rather as sub-syndromal clusters of symptoms that vary over time (Tariot, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They often do not present as discrete psychiatric diagnoses but rather as sub-syndromal clusters of symptoms that vary over time (Tariot, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Anticonvulsants such as carbamazepine and valproate have been used successfully in the management of agitation and aggression in dementia, being less neurotoxic than lithium (Tariot, 1999). A small placebocontrolled trial of carbamazepine in 51 patients with dementia showed significant improvement in agitation and aggression, the side-effects being common but mild (Tariot et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations